The Effect Of Umbilical Cord Milking In Reducing ROP Of Preterm Babies. - Md. Abdul Mannan; Shamima Akhter; Ummey Tamima Nasrin; Tariq Reza Ali; Nuzhat Chowdhury; Md. Sharfuddin Ahmed (International Journal of Medical Research and Review, 2023)
Background: Recent advances in neonatal care in the last decade have improved the survival rates for premature infants. Consequently, the incidence of ROP has increased in parallel. ROP is under constant epidemiological study around the world. Prematurity, low birth weight, respiratory distress syndrome, mechanical ventilation, prolonged oxygen treatment and blood transfusion increase the risk of ROP. Umbilical cord milking reduces the incidence of ROP in preterm infants by reducing the need for blood transfusions in preterm infants. Objective: To observe effect of ROP with umbilical cord milking. Methodology: This prospective observational study was carried out on neonates, in the Department of Neonatology, BSMMU after approval from IRB. Neonates admitted into neonatal intensive care unit of BSMMU satisfying the inclusion and exclusion criteria was enrolled for the study. A written informed consent was taken from parents and assurance about confidentiality was given. Neonates born before 37 weeks of gestation was assigned to either umbilical cord milking or non-milking group at a 1: 1 ratio according to a computer generated randomized sequence. After delivery of a baby umbilical cord milking was performed by holding the infant at the level of the placenta. First eye evaluation for ROP was done at 20 days of age for gestational age less than 30weeks & weight below 1200gm & at 30 days of age for gestational age more than 30 weeks & above weight 1200gm. Follow-up was continued until retinal vascularization was completed. The follow-up schedules were organized depending on the retinal findings. The retinal finding was evaluated according to the International Classification of Retinopathy of Prematurity. The patients were grouped as no ROP, mild ROP (stages I-II ROP without plus disease, showed regression), and severe ROP (zone 1 or zone 2, stage III, aggressive ROP without stages, stage II with plus disease who required treatment). Data were recorded in a preformed questionnaire and data were analyzed by statistical package for social sciences (SPSS) version 20. Results: 114 newborns were enrolled in this study. Then among 114 preterm neonates 57 were randomized to umbilical cord milking group and 57 were randomized to no milking group. Baseline characteristics were almost similar between the two groups. There were significant increase is hematocrit level 57.3 ±3.5 V 47.4 ± 4.5 (P value less than 0.001), reduction in need of blood transfusion 3.5% V 42.1% (P value less than 0.001) & reduction in ROP 3.5% V 19.3% (P 0.007). Conclusion: This study concluded that umbilical cord milking after delivery improves hematocrit level, reduces need of blood transfusion & reduces the incidence of ROP in preterm infant.